Effects of standardized ileal digestible lysine level and added tribasic copper chloride on growth performance, carcass characteristics, and economics in finishing pigs - Coble, Kyle F.; Dritz, Steven S.; Usry, J.; Tokach, Michael D.; DeRouchey, Joel M.; Goodband, Robert D.; Woodworth, Jason C. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2015)
A total of 1,267 pigs (PIC 337 × 1050; initially 58.3 lb) were used in a 120-d study. Before initiating the trial, pigs were fed a common diet for 9 d containing 188 ppm Cu from tribasic copper chloride (TBCC). On d 0, pens of pigs were allotted to 1 of 8 dietary treatments in a randomized complete block design with 26 to 27 pigs (similar number of barrows and gilts) per pen and 6 pens per treatment. Treatments were arranged in a split-plot design. Whole-plot treatments were 2 levels of the estimated standardized ileal digestible lysine (SID Lys) requirement (92.5 or 100%). Within each level of Lys, there was a 2 × 2 factorial arrangement of treatments with either 0 or 150 ppm Cu from TBCC with two feeding durations (60 or 120 d). All diets were corn-soybean meal–based with 30% dried distillers grains with solubles (DDGS) and contained 17 ppm of Cu from copper sulfate (CuSO4) provided by the trace mineral premix. Overall (d 0 to 120), no TBCC × SID Lys interactions were observed for growth performance, final BW, or caloric efficiency. Pigs fed 100% of the SID Lys requirement had increased (P < 0.05) ADG and final BW as well as improved F/G, compared with those fed 92.5% of the estimated requirement. The improvements in F/G also led to improvements in caloric efficiency on both an ME and NE basis. For carcass characteristics, a significant TBCC × SID Lys interaction (P < 0.05) was observed for carcass yield and backfat depth. Hot carcass weight and ADG were improved (P < 0.05) in pigs fed 100% SID Lys compared with those fed 92.5% and tended (P < 0.10) to improve in pigs fed TBCC compared with those not fed TBCC. Economically, pigs fed 92.5% of their SID Lys requirement had lower (P < 0.05) total feed cost, cost per pound of gain, and value of the weight gained during the experiment (gain value) compared with those fed 100% SID Lys. Despite the increased feed cost, income over feed cost (IOFC) was greater (P < 0.05) for pigs fed 100% compared with those fed 92.5% of the estimated Lys requirement. When economics were calculated on a constant weight basis, pigs fed 92.5% SID Lys had poorer (P < 0.05) adjusted F/G. The lower ADG for pigs fed 92.5% of their SID Lys requirement resulted in an increase (P < 0.05) in facility cost compared with those fed 100% of their SID Lys requirement because of the increased time required for those pigs to reach the assumed market weight of 275 lb. In conclusion, increasing SID Lys from 92.5 to 100% resulted in increased ADG, HCW, HCW ADG, and improved F/G. There were no differences among pigs fed different TBCC feeding strategies, but pigs fed 150 ppm Cu from TBCC had increased yield and HCW, which led to an increase in HCW ADG and improved HCW F/G.
Swine Industry Day, 2014 is known as Swine Day, 2014
Keywords: Copper; Finishing pig; Lysine